Blockchain sukuk regulation via regtech & shariahtech - Adam Sa'ad, Auwal; Sherin, Kunhibava; Aishath, Muneeza; Ershadul, Kareem; Zakariyya, Mustapha (2019)
The advent of Industrial revolution 4.0 has resulted in unprecedented use of financial technology (fintech) to facilitate, produce and/or deliver financial products. Fintech is used by technology start-ups and incumbent financial institutions in developing innovative financial products and services while leveraging on such technologies as artificial intelligence (AI) and smart contracts on blockchain etc. A blockchain is a decentralized, distributed and digital ledger that records transactions in form of blocks across many computers such that the record cannot be altered retroactively, without change to all subsequent blocks. A smart contract is an automation protocol that encodes and apply business rules agreed by parties directly into the underlying transaction itself and the blockchain enforces the contract rules. The use of blockchain and smart contracts revolutionize the financial services industry and has made possible the transformation and emergence of sukuk (Islamic bond) in ICM. The ICM is a highly regulated market and the emergence of blockchain sukuk defies extant regulatory framework governing operations of classical sukuk. This brings to light the need for a suitable mechanism of regulation to address associated regulatory, legal and Shariah issues. Hence, the case for regtech and Shariah. While regtech is the use of technology to regulate and facilitate compliance with legal and regulatory requirements, Shariatech is a specially tailored regtech to ensure end-to-end Shariah compliance in sukuk operations.